2007
DOI: 10.1111/j.1600-051x.2006.01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet‐rich plasma on the healing of intra‐bony defects treated with a natural bone mineral and a collagen membrane

Abstract: Within its limits, the present study has shown that (i) at 1 year after regenerative surgery with both NBM+PRP+GTR and NBM+GTR, significant PD reductions and CAL gains were found, and (ii) the use of PRP has failed to improve the results obtained with NBM+GTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 40 publications
6
96
0
7
Order By: Relevance
“…[27] Whereas, in both the studies of Döri et al . [2829] no significant difference in pocket reduction and CAL gain between the two groups were reported. The difference could be attributed to the reason that no blood parameters were evaluated, which may entail the risk of production of PRP volumes with low PCs leading to disappointing results.…”
Section: Discussionmentioning
confidence: 94%
“…[27] Whereas, in both the studies of Döri et al . [2829] no significant difference in pocket reduction and CAL gain between the two groups were reported. The difference could be attributed to the reason that no blood parameters were evaluated, which may entail the risk of production of PRP volumes with low PCs leading to disappointing results.…”
Section: Discussionmentioning
confidence: 94%
“…[10121314] The positive impact of PRP on bone healing is attributed to angiogenic, proliferate and differentiating effect of PDGF and TGF present in high concentration. However, there is pausity of information about the clinical efficacy of PRP in repair and regeneration of periodontal defect.…”
Section: Discussionmentioning
confidence: 99%
“…But when the local conditions are not optimum, PRP gels alone are not strong enough to promote a clinical filling equivalent to the dense bone filling reached with a bone substitute [50]. Most of the randomized controlled clinical trials(RCTs) demonstrated that the addition of PRP to certain regenerative materials, doi: 10.7243/2050-1218-2-11 namely bioactive glass [51], b-TCP [52], BM and e-PTFE membranes [53], b-TCP and e-PTFE membranes [54], BM and collagen membranes [23] and BM and EMD [55], failed to confer statistically significant additive benefits in the therapy of periodontal intraosseous defects. However, according to other RCTs such adjunctive positive outcomes may result from other combinations of PRP, namely together with BM [28], DFDBA [56] and hydroxyapatite [22].…”
Section: Discussionmentioning
confidence: 99%